Raziskanost narečne slovenščine: obstoječe in potrebno - Smole, Vera (Slavia Centralis, 2020)
Exploration of dialectal Slovene: the existing and necessaryThis paper presents and analyses the results of empirical research (online survey) created in the framework of the CRP Jezikovna politika republike Slovenije in potrebe uporabnikov 'Language Policy of the Republic of Slovenia and the needs of users'. In the paper we are only interested in the part that gives us an insight into how much users know and use handbooks and manuals on Slovenian dialects, what they need and what they prefer. The results of a shorter and even more targeted survey on a very small sample have also been added.
Keywords: intangible cultural heritage; Slovenian dialects; linguistic needs of users; empirical research; dialect dictionary; linguistic atlas; dialect texts